Sport activity and the risk of breast cancer: results from a case - control study - J Kruk (Biology of Sport, 2003)
A case – control study of 257 women with breast cancer and 565 control women was conducted to investigate the effect of life-time sport activity on breast cancer risk. Information was collected by questionnaire about sports played, frequency of participation and duration. The activity levels were determined using frequency variable weighted for metabolic equivalents of energy expenditure (MET). Multivariate logistic regression analyses were used to compute odds ratios (ORs) and 95% confidence intervals (CIs). A full assessment of confounding and effect modification was undertaken. The odds ratios for increasing tertiles of sport activity were 1.00 (referent), 0.50 (CI: 0.33-0.76) and 0.44 (CI: 0.28-0.64), respectively (P-trend = 0.000). Comparing sport active women to inactive women the OR was 0.49 (CI: 0.35-0.69). Models stratified according to body mass index, age at menarche, age at first full term pregnancy, intake of vegetables and fruits, and experience of stress were examined. In models stratified the risks of breast cancer were also reduced with higher levels of activity in sport. The conclusion is that women who participated in sports have a reduced risk of breast cancer.